Biosintetis Etilen Luka pada Irisan Mesokarp Labu Kuning - Murdijati Gardjito; Mochamad Adnan; Tranggono Tranggono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
The objectives of this study w to obtain new informations to complete the pathway in wounded ethylene biosynthesis and metabolism in the wound tissue of the mesocarp of the winter squash fruit. The samples were in the term of mesocarp cylinder showing the ratio of wound area and the tissue weight of 4.5 cm2/g and mesocarp disk for the ratio of 15.5 cne/g respectively. Experiments in this study were conducted in continuous phase of 44 hours using flowthrough system at 25Â°C. Analyses and measuremets were done for ethylene, 1 amino cyclopropane- 1 -carboxylic acid (ACC), malonil-ACC (MACC), HCN, phenolics, 1 amino cyclopropane-1 -carboxylic acid oxidase (ACC-oxidase), and a cyano alanine sythase (b-CAS) enzymes at certain time interval. The extent of ethylene production was directly related to the availability of its precusor (ACC) and ethylene-forming enzyme or ACC-oxidase. It was also found that no malonization of ACC occured during biosynthesis of wound ethylene. The result also indicated that the formation of wound ethylene was followed by the formation of cyanide-containing compounds with the similar pattern and an incrase in b-CAS activity suggesting cyanide detoxification in the tissue. Larger wound surface area ratio made the b-CAS activity was higher.